Análises físico-químicas, identificação e quantificação de hidrocarbonetos policíclicos aromáticos em cachaças envasadas em garrafas de poli-tereftalato de etileno - Souza, Rafaella Hilda Zaniti (2019)
Cachaça is a beverage of great economic and cultural importance for Brazil. In addition to the main compounds, carbon dioxide and ethanol, the secondary compounds responsible for the beverage bouquet are produced. In parallel, other toxic substances can be produced, and these compounds interfere with the commercialization and exportation of a quality product. Among the contaminants, Aromatic Polycyclic Hydrocarbons (APH’s) with two or more aromatic rings, commonly found in beverages and foods, have been investigated for their mutagenic and carcinogenic properties. APH's can be produced in cachaças from the chemical decomposition of carbohydrates, and they can originate in different stages of the process of production and storage of the drink. Because of several convenient features, PET packaging has been widely used for storing beverages, including cachaça. However, there are several concerns related to the use of these packages for these beverages, such as the possible migration of constituents into the contents, favoring the interaction of packaging with the product, and the proof that plastic packaging can be sources of contamination by APH's. Thus, the objective of this work was to evaluate the physical and chemical quality of five brands of cachaças from the State of Minas Gerais, as well as to study and correlate the formation and quantification of APH's of these samples after eight months of storage in PET bottles. The physicochemical analyses were performed according to the methods recommended by the Ministry of Livestock and Supply (MAPA). The packages influenced the concentration of the compounds in at least one brand of cachaça for all the parameters analyzed, and the parameters that presented the greatest discrepancies were alcohol content, acidity and furfural. Ethyl carbamate was not detected in any of the samples. In the quantification of APH's by HPLC, the types of packages interfered in the quantification of these contaminants, so that the samples packed for a longer time in PET packaging contained higher concentrations of these contaminants in all the brands of cachaça. The concentrations of these contaminants were proportional to the duration of conditioning in these packages. This observation indicates that this type of packaging is not always ideal for the storage of cachaça.